2022
DOI: 10.1007/s00253-021-11722-z
|View full text |Cite
|
Sign up to set email alerts
|

Generation and functional analysis of single chain variable fragments (scFvs) targeting the nucleocapsid protein of Porcine epidemic diarrhea virus

Abstract: Porcine epidemic diarrhea virus (PEDV) is the causative agent of porcine epidemic diarrhea, which can cause death in suckling piglets. Vaccines confer only partial protection against new mutant strains, whereas antibodies targeting virus-encoded proteins may be effective prophylactics. In this study, we constructed a recombinant single chain variable fragment (scFv) library from the spleens of two pigs immunized with a recombinant PEDV nucleocapsid (N) protein. Among the positive clones directed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…Several studies reported that PEDV replication was suppressed when the N protein was degraded (49,58,59). Our scFvs targeting the PEDV N protein significantly suppressed PEDV replication in PEDV-infected cells, as described in our previous study (36). Previous studies indicated that PEDV infection in piglets caused fecal viral RNA shedding (39,60).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Several studies reported that PEDV replication was suppressed when the N protein was degraded (49,58,59). Our scFvs targeting the PEDV N protein significantly suppressed PEDV replication in PEDV-infected cells, as described in our previous study (36). Previous studies indicated that PEDV infection in piglets caused fecal viral RNA shedding (39,60).…”
Section: Discussionsupporting
confidence: 74%
“…ScFvs targeting the PEDV N protein were previously generated and described ( 36 ). Briefly, a porcine recombinant scFv library was constructed and four scFvs targeting the PEDV N protein were generated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations